Analisis Hubungan Penyebaran Lindi TPA Sumurbatu terhadap Kualitas Air Tanah di Kelurahan Sumurbatu Kecamatan Bantar Gebang Bekasi Tahun 2017 - Arum, Annisa Retno; Rahardjo, Mursid; Yunita, Nikie Astorina (Fakultas Kesehatan Masyarakat, 2017)
Sumurbatu Landfill still using open dumping system at managing their wastes. Open dumping method has negative effect for groundwater quality around because there were leachate pollution that can make environmental damaged and detracted human health. Preliminary survey showed that nitrate value for groundwater around Sumurbatu Landfill almost exceed the standard which was equal to 8,59. Data of Bantar Gebang health center at 2014 until 2016 year showed that there were an increase in patient visits in diarrheal diseases which the amount was 3.034, these problem allowed that there were pollution indication in groundwater around Sumurbatu Landfill caused by leachate. The purpose of this research was to analyze the correlation between leachate spreading with groundwater quality include pH, COD and nitrat parameter in Sumurbatu Village, Bekasi 2017. This research was a quantitative analytical approach with cross sectional design. Sample of this research were 32 house that using groundwater for their daily needs which is located in the north of Sumurbatu Landfill. Data was analyzed by Rank Spearman and Pearson Product Moment. Statistical test results for leachate spreading showet p value was 0,000 for nitrate value and 0,481 and 0,174 respectively for COD and pH with very low permeability value. The conclusion of this research was there were correlation between leachate spreading with nitrate value and there weren’t correlation between leachate spreading with COD and pH value and soil absorption around landfill was really hard to slip off water.This research recommended Sumurbatu inhibitants more active to controlled groundwater quality that they used.